Performance of La0.6Sr0.4Co1−yFeyO3 (y=0.2, 0.5 and 0.8) nanostructured cathodes for intermediate-temperature solid-oxide fuel cells: Influence of microstructure and composition. Issue 2 (1st February 2016) - Mejía Gómez, Augusto; Sacanell, Joaquín; Leyva, Ana Gabriela; Lamas, Diego G.
Abstract: We investigated the electrochemical properties of Co–Fe perovskites, which can be used as cathodes for intermediate-temperature solid-oxide fuel cells (IT-SOFCs). We studied the electrochemical properties of nanostructured mixed ionic-electronic conductors for IT-SOFC cathodes with compositions of La0.6 Sr0.4 Co1− y Fe y O3 ( y =0.2, 0.5 and 0.8). We analyzed the performance of two types of nanostructures: nanorods and nanotubes. Our results show that the electrochemical performance is highly influenced by the form of nanostructure, whereas the effect of composition is less significant.